2017
DOI: 10.1186/s12891-017-1892-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of proximal humerus fractures, surgical procedures and outcomes among elderly hospitalized patients with and without type 2 diabetes in Spain (2001–2013)

Abstract: BackgroundSeveral studies have reported that diabetic persons have an increased risk for fractures than non-diabetes patients. The association between proximal humerus fractures and type 2 diabetes (T2DM) is unclear and some studies point to insulin treatment, hypoglycaemic episodes consequently to inadequate control of diabetes or, more recently, to an alteration of trabecular bone. We examined trends in the incidence of proximal humerus fractures, surgical procedures and outcomes among hospitalized patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…We conducted a survey of patients aged ≥65 years with newly diagnosed PHFs in South Korea between 2008 and 2016 [7, 21, 22]. First, patients with PHFs who received surgical treatment were identified with the ICD-10 codes (S42.2) and the operation codes (ORIF: N0602 and N0612; CRIF: N0992; HA: N2711 and N2716; RSA: N2071 and N2076) from the HIRA database (Table 1) [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a survey of patients aged ≥65 years with newly diagnosed PHFs in South Korea between 2008 and 2016 [7, 21, 22]. First, patients with PHFs who received surgical treatment were identified with the ICD-10 codes (S42.2) and the operation codes (ORIF: N0602 and N0612; CRIF: N0992; HA: N2711 and N2716; RSA: N2071 and N2076) from the HIRA database (Table 1) [23].…”
Section: Methodsmentioning
confidence: 99%
“…The HIRA data for 2007 was required to ensure that the observed PHFs were not recurrent entries of fractures that had occurred before 2008 [7]. To avoid multiple counting of ICD-10 codes for PHFs that were conservatively treated more than once during the study period, only the data obtained when the ICD-10 code was first entered for each patient were included [21].…”
Section: Methodsmentioning
confidence: 99%
“…The annual percentage changes (APCs) in the age-adjusted incidence rates of isolated SLAP repair from 2008 to 2017 were calculated using joinpoint regression analysis (Joinpoint Regression Program, version 4.3.1.0; National Cancer Institute, Bethesda, MD, USA). 14,16 All other data sets were analyzed using SAS statistical software version 9.13 (SAS Institute, Cary, NC, USA). Univariate analysis was conducted using t-test.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the epidemiology of the more common upper extremity fractures [2] particularly wrist [3], hand [4] and proximal humerus fractures [5,6], while other upper extremity fractures have been rarely described. None of these studies have focused on a rst presenting fracture.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of DRF epidemiology examined nine publications addressing secondary risk, that concluded that a prior wrist fracture was associated with approximately a doubling of risk for subsequent fractures [5]. Increasing rates of DRF in both working ages and older adults [6], is a concern for health care cost containment. Hand fracture rates have also been described, and the burden relates to costs and occupational impacts [7,8].…”
Section: Introductionmentioning
confidence: 99%